Simulation of wind power with front-end converter into interconnected grid system - Sharad W. Mohod; Mohan V. Aware (Journal of Industrial Engineering and Management (JIEM), 2009)
In the growing electricity supply industry and open access market for electricity worldwide, renewable sources are getting added into the grid system. This affects the grid power quality. To assess the impact on grid due to wind energy integration, the knowledge of electrical characteristic of wind turbine and associated control equipments are required. The paper presents a simulation set-up for wind turbine in MATLAB / SIMULINK, with front end converter and interconnected system. The presented control scheme provides the wind power flow to the grid through a converter. The injected power in the system at the point of common coupling is ensured within the power quality norms.
Keywords: 650; power quality; wind generating system